2016
DOI: 10.1128/jb.00845-15
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes Associated with the Essential Diadenylate Cyclase CdaA and Its Potential Regulator CdaR in the Human Pathogen Listeria monocytogenes

Abstract: Cyclic diadenylate monophosphate (c-di-AMP) is a second messenger utilized by diverse bacteria. In many species, including the Gram-positive human pathogen Listeria monocytogenes, c-di-AMP is essential for growth. Here we show that the single diadenylate cyclase of L. monocytogenes, CdaA, is an integral membrane protein that interacts with its potential regulatory protein, CdaR, via the transmembrane protein domain. The presence of the CdaR protein is not required for the membrane localization and abundance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 50 publications
(102 reference statements)
1
69
0
2
Order By: Relevance
“…YbbR homologs have been shown to directly interact with DacA homologs (also referred to as CdaA) in other bacteria (2123). In addition, an interaction between CdaA and GlmM has been reported, leading to the hypothesis that DacA, YbbR, and GlmM form a three-protein complex (22, 32) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YbbR homologs have been shown to directly interact with DacA homologs (also referred to as CdaA) in other bacteria (2123). In addition, an interaction between CdaA and GlmM has been reported, leading to the hypothesis that DacA, YbbR, and GlmM form a three-protein complex (22, 32) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This product is subsequently used for the production of an early peptidoglycan synthesis intermediate. The second gene in the operon, ybbR , encodes a predicted membrane protein that has been shown to interact with, and influence the activity of DacA (2123). However, there are conflicting reports as to whether YbbR stimulates or inhibits the activity of the cyclase.…”
Section: Introductionmentioning
confidence: 99%
“…Increased intracellular c-di-AMP levels in bacteria have been associated with increased tolerance to a wide range of environmental challenges, including cell wall damage, high temperatures, starvation, and acid stress, as well as some antibiotics, including lysostaphin, oxacillin, and penicillin G (4,11,12). While many genes regulated by c-di-AMP have been reported (10), the signal transduction pathways that convert environment stresses to c-di-AMP signals have not been identified, though it has been suggested that membrane-associated enzymes such as c-di-AMP synthase A (CdaA, also referred as YbbP) and its regulator CdaR (c-di-AMP synthase A regulator, also referred to as YybR) may sense damage directly (2,7,13). The cyclic dinucleotide signaling pathway and its potential role in stress response have not been characterized in enterococci.…”
mentioning
confidence: 99%
“…A Streptococcus suis mutant tolerating large amounts of lysozyme had acquired a mutation in the cdaA diadenylate cyclase gene, which probably alters the cellular c-di-AMP concentration (36). In contrast, a decrease of the cellular c-di-AMP levels in B. subtilis and L. monocytogenes caused cell lysis (2,7,17). Moreover, strains that synthesize smaller amounts of c-di-AMP are more susceptible to cell wall-targeting antibiotics (15).…”
Section: C-di-amp a Key Player In Controlling Osmolyte Transport In mentioning
confidence: 99%
“…Moreover, strains that synthesize smaller amounts of c-di-AMP are more susceptible to cell wall-targeting antibiotics (15). Therefore, it has been concluded that c-di-AMP is essential for proper cell envelope synthesis (2,7,35). However, today we know that the nucleotide rather indirectly affects the integrity of the cell envelope by modulating the cellular turgor, a physical variable that has to be tightly adjusted depending on the osmotic pressure of the environment (15).…”
Section: C-di-amp a Key Player In Controlling Osmolyte Transport In mentioning
confidence: 99%